A primary care-based asthma program improves recognition and treatment of persistent asthma in inner-city children compared to routine care. (20th October 2016) - Warman, Karen; Silver, Ellen
Abstract: Objective : To examine whether a primary care-based asthma program that applies the Expert Panel Report 3 (EPR-3): Guidelines for the Diagnosis and Management of Asthma-2007 criteria to classify asthma severity increases detection of persistent asthma in inner-city children and affects "step of care" compared to routine care. Methods : A retrospective chart review was conducted of 97 consecutive children referred to the asthma program from 2011–2013. Asthma severity documented during routine health care maintenance visits was compared to the asthma severity assessed during the asthma program visit using five standardized questions and spirometry. Medication plan "step of care" was compared pre- and post- the asthma program visit. Results : 79 children, ages 5–19 years old (mean = 9.6), had spirometry tracings meeting American Thoracic Society criteria and were included in this study. 53% were male. The majority of children were Latino (45.6%) or African American (35.4%). At the asthma program visit, more children were identified with moderate or severe persistent asthma based upon clinical questions (47.9%), spirometry (56.9%) or combined criteria (75.3%) than had been identified during routine care (15.2%); all p < .05. After the asthma program visit, more children were prescribed controller medications (82.3% vs 63.3%; p < .05) and 40.6% had their medication plan stepped up. Conclusions : In this population of inner-city children, asthma severity was under-recognized and undertreated during routine care. A primary care based asthma program, which formalized applying EPR-3 criteria, increased detection of persistent asthma and led to "step-ups" in treatment plans.